Penerapan Kegiatan Melipat Kertas Dalam Meningkatkan Aspek Perkembangan Motorik Halus Anak di Kelompok Bermain As-Syifa - Nursiah; Yayan Ridwan; Hadisa Putri (Tarbiya Islamica, 2023)
The aim of this research is to analyze paper folding activities in improving aspects of children's fine motoric development, analyze the implementation of paper folding activities in improving aspects of fine motoric development and evaluate paper folding activities in improving aspects of children's fine motoric development at KB As-Syifa. The method used in the research uses qualitative and phenomenological research. Data collection techniques use observation, interviews and documentation. The analysis techniques used are data reduction, data display and data verification and drawing conclusions. Based on research results; folding paper into birds, folding paper into folds of clothes (clothing), and folding paper into boats. The paper folding activity starts from the initial activity at 13:00-13:40, standing in rows, reading daily prayers, singing. Then the main activities are 13:40-14:30. Then continue with hand washing and eating breaks at 14:30-14:40. Lastly is the closing activity from 14:40-15:00 asking about today's mood, informing about tomorrow's activities, singing and praying. Evaluation of paper folding activities in improving aspects of children's fine motor development at the As-Syifa KB, namely using the assessment scale Developing Very Well (BSB), Developing According to Expectations (BSH), Starting to Develop (MB), and Not Yet Developing (BB)